2013
DOI: 10.1177/1087057112464574
|View full text |Cite
|
Sign up to set email alerts
|

Visible-to-Near IR Quantum Dot–Based Hypermulticolor High-Content Screening of Herbal Medicines for the Efficacy Monitoring of Hair Growth Promotion and Hair Loss Inhibition

Abstract: There is a growing interest in alopecia prevention strategies, as the number of alopecia patients is increasing. We examine the efficacy of herbal medicine for hair growth promotion/hair loss inhibition in two cell lines via Western blot and highcontent screening (HCS). Nine herbal extracts were obtained from three different herbal medicine mixtures using 3 different extraction methods. Five target proteins-IGF-1 (insulin-like growth factor-1), TGF-β2 (transforming growth factor-β2), VEGF (vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
10
0
3
Order By: Relevance
“…It also led to choosing two treatment periods for our study. Cell proliferation was studied for 24 h and 48 h. The treatment period of 24 h was chosen because several previous studies have shown that after 24 h, minoxidil already exerts proliferative properties on hair follicles and DP cells [ 35 , 36 ]. Nevertheless, a 48-h long treatment gave a perspective on the efficiency of our extracts over a longer period.…”
Section: Resultsmentioning
confidence: 99%
“…It also led to choosing two treatment periods for our study. Cell proliferation was studied for 24 h and 48 h. The treatment period of 24 h was chosen because several previous studies have shown that after 24 h, minoxidil already exerts proliferative properties on hair follicles and DP cells [ 35 , 36 ]. Nevertheless, a 48-h long treatment gave a perspective on the efficiency of our extracts over a longer period.…”
Section: Resultsmentioning
confidence: 99%
“…Yano et al [11] identified VEGF as a major mediator of hair follicle growth and cycling and provided the first direct evidence that improving follicle vascularization promoted hair growth and increased hair follicle and hair size in mice. It is known that VEGF is a growth factor that stimulates vasculogenesis and angiogenesis, stimulating hair growth by facilitating the supply of nutrients to the hair follicle, providing even an increase in the base of the follicle diameter [5,12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…Minoxidil is a clinically used hair growth promoter that enhances hair KC proliferation and activates hDP cells to induce growth factors 44 . IGF-1 is among these growth factors, and has been shown to exhibit a potent hair elongation effect 45 46 47 48 . To examine whether iDPSCs would be useful for future drug discovery for hair diseases, their pharmacological response to minoxidil was compared with that of hDP cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%